2019
DOI: 10.1001/jamasurg.2018.5249
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Collagen Signature in the Tumor Microenvironment With Lymph Node Metastasis in Early Gastric Cancer

Abstract: IMPORTANCE Lymph node status is the primary determinant in treatment decision making in early gastric cancer (EGC). Current evaluation methods are not adequate for estimating lymph node metastasis (LNM) in EGC. OBJECTIVE To develop and validate a prediction model based on a fully quantitative collagen signature in the tumor microenvironment to estimate the individual risk of LNM in EGC. DESIGN, SETTING, AND PARTICIPANTS This retrospective study was conducted from August 1, 2016, to May 10, 2018, at 2 medical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 48 publications
1
102
0
1
Order By: Relevance
“…Nevertheless, although the cN status was more advanced in the pathologist group, the pN status was not significantly different between the two groups. These results contradict the fact that the more advanced the depth of tumor invasion is, the more advanced the LN status becomes in GC (22)(23)(24)(25). Since our trial excluded patients with preoperative chemotherapy or D1/D1+ gastrectomy, we speculated that the inconsistency between cN and pN could be attributed to the methods of LN examination.…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, although the cN status was more advanced in the pathologist group, the pN status was not significantly different between the two groups. These results contradict the fact that the more advanced the depth of tumor invasion is, the more advanced the LN status becomes in GC (22)(23)(24)(25). Since our trial excluded patients with preoperative chemotherapy or D1/D1+ gastrectomy, we speculated that the inconsistency between cN and pN could be attributed to the methods of LN examination.…”
Section: Discussionmentioning
confidence: 64%
“…It has been shown that mature CAFs may produce more collagen I and IL-8 (29). Abundant collagen I increases the stiffness of tumor stroma and the internal pressure of the tumor, which results in the rupture of tumor cells and paves the way for the spread or metastasis of cancer cells together with the regular alignment of fibers (30,31). The increased stromal stiffness aggravates hypoxic TME, which promotes neutrophil polarization and inhibits its apoptosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, accurate prediction of lymph node involvement is essential in helping doctors make decisions more reasonably [20,[25][26][27][28][29]. Treatment recommendations for a patient with GC would vary depending on lymph node status.…”
Section: Discussionmentioning
confidence: 99%